Assessing digital and info-communication competencies in higher education: A blended approach for e-learning environments - Correia, J. D.; Henriques, S. (Perspectives and trends in education and technology: Selected papers from ICITED25, 2025)
In an era increasingly shaped by information and communication technologies, assessing digital and info-communication competencies among students has become a focal point for academic and institutional initiatives. Various projects, both within and outside Academia, have sought to classify students’ competencies at different levels, often relying on standardized tests and self-assessment questionnaires. However, as technological advancements rapidly evolve, universities face mounting pressure to align educational strategies with high levels of digital and info-communication proficiency and with the competitive demands of the labor market. It is, therefore, important to study these assessment tools further. Blended assessment methods, combining practical tests with self-perception questionnaires, offer a more nuanced evaluation of students’ digital competencies. By integrating objective skills assessments with self-reported proficiency, this approach captures a broader spectrum of abilities, recognizing the influence of diverse teaching models, students’ academic backgrounds, prior digital exposure, and access to technological resources. This is particularly relevant in distance higher education, where continuous engagement in virtual learning environments provides ongoing opportunities for monitoring digital and info-communication competencies development. Despite growing academic interest in this field, empirical research on digital and info-communication competencies in Portuguese higher education, particularly in e-learning contexts, remains limited. This paper presents the development of a digital literacy test and a questionnaire designed to assess students’ digital and info-communication practices. These instruments were created as part of the ongoing research project Digital and Infocommunicational Competencies in Virtual Learning Environments: Practices in e-Learning Curricular Units in Portuguese Higher Education.